Evaluasi Terminal Tipe A - Willy Ananias Gara (W.A. Gara) Kota Palangkaraya: Terminal Evaluation Type A - Willy Ananias Gara (W.A. Gara) Palangkaraya City - Baktiani, Linda (Media Ilmiah Teknik Sipil, 2022)
The study aims to find factors that generated the ineffective utilization of W.A Gara bus station as the only type A bus station in Palangka Raya and find the strategies for more effective utilization. The study was conducted by using the quantitative-qualitative analysis technique. Primary data was obtained by distributing the questionnaires to the service users who would conduct trips using the bus. The secondary data was obtained from related institutions to support data that facilitated analyzing the problems. The study found that several factors generated ineffective utilization of the bus station, namely location factor, accessibility factor, and security and convenience factor. The strategies proposed in this research to make more effective utilization of the bus station were: first, creating an attraction which expected to be able to attract the passengers to enter the bus station; second, establishing system on the accessibility of the bus station; third, improving service quality to facilitate and attract the passengers to get on and off the bus in the bus station; forth, designing the more convenient concept of the bus station to attract people to the bus station and implementing control toward the bus agencies so that the process of passengers’ get on and off the bus could occur in the bus station; fifth, improving security monitoring in the bus station